2008
DOI: 10.1177/1934578x0800300317
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation of Pimarane and Isopimarane Diterpenoids: The 13C NMR Contribution

Abstract: This paper is dedicated to Professor P. Joseph-Nathan for his 65 th birthday. 13 C NMR spectroscopy is actually one of the first tools used for the structural elucidation of natural and synthetic compounds and it is also used in biosynthetic studies. The aim of this review is to present the 13 C NMR assignments of a large number of pimarane diterpenoids, describing the most significant effects caused by different substitution patterns and different stereochemistry at their chiral centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 95 publications
(184 reference statements)
0
9
0
Order By: Relevance
“…These data indicated the same orientation of H‐1, H‐14, Me‐17, Me‐19, and Me‐20. Based on 1,3‐diaxial interaction, the chemical shifts of C‐17 (δ C 21.7), C‐19 (δ C 21.7), and C‐20 (δ C 21.7) were more shielded than C‐18 (δ C 33.15); these data suggested the β‐orientation (Seca, Pinto, & Silva, ) and the axial position (Rasoamiaranjanahary, Guilet, Marston, Randimbivololona, & Hostettmann, ) of these methyl groups. Hence, 7 was defined as a new isopimarane diterpene named 1α‐hydroxy‐14α‐methoxyisopimara‐8,15‐diene (see S29–S38).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These data indicated the same orientation of H‐1, H‐14, Me‐17, Me‐19, and Me‐20. Based on 1,3‐diaxial interaction, the chemical shifts of C‐17 (δ C 21.7), C‐19 (δ C 21.7), and C‐20 (δ C 21.7) were more shielded than C‐18 (δ C 33.15); these data suggested the β‐orientation (Seca, Pinto, & Silva, ) and the axial position (Rasoamiaranjanahary, Guilet, Marston, Randimbivololona, & Hostettmann, ) of these methyl groups. Hence, 7 was defined as a new isopimarane diterpene named 1α‐hydroxy‐14α‐methoxyisopimara‐8,15‐diene (see S29–S38).…”
Section: Resultsmentioning
confidence: 96%
“…The HMBC spectra ( Figure 2) showed correlations between H-1 (δ H 3.81) and C-3 (δ C 34.4), C-5 (δ C 44.2) ; H-3β (δ H 1.17), Me-20 (δ H 1.02) and C-1 (δ C 71.2); H-14 (δ H 2.99) and C-7 (δ C 30.3), C-8 (δ C 131.9), C-9(δ C 137.6), C-13 (δ C 40.5); H-15 (δ H 5.74), Me-17 (δ H 1.08) and C-13, C-14 (δ C 84.7); and OMe-21 (δ H 3.51) and C-14. In addition, COSY spectra (Figure 2) 1,3-diaxial interaction, the chemical shifts of C-17 (δ C 21.7), C-19 (δ C 21.7), and C-20 (δ C 21.7) were more shielded than C-18 (δ C 33.15); these data suggested the β-orientation (Seca, Pinto, & Silva, 2008) and the axial position (Rasoamiaranjanahary, Guilet, Marston, Randimbivololona, & Hostettmann, 2003) of these methyl groups.…”
Section: Isolated Compoundsmentioning
confidence: 94%
“…The relative configuration at C-13 was assigned by comparison of the 13 C NMR data with those of isopimarane diterpenoids [22]. In the Δ 7,15 isopimaradiene skeleton, a methyl with a β-orientation at C-13 appears at δ C~2 2, which is further upfield than the resonance of an α-equatorial one [23]. Thus, a β-axial position was established for the methyl group (C-17) and an α-equatorial position was established for the vinyl group.…”
Section: Resultsmentioning
confidence: 99%
“…The deshielded carbon resonances of two quaternary sp2 carbons (C-8 at δ 129.1 and C-9 at δ 165.8) indicated conjugation of a tetra-substituted C=C double bond with the carbonyl group [31], whose position was confirmed at C-7 by the 1H–13C long-range correlations between the protons H-14 β /H-14 α and the carbonyl carbon (Figure 2; Figure S13, Supplementary Materials). The presence of a hydroxyl group as already suggested by the mass spectrum showing a fragment at m/z 285.2222 [M + H − H2O]+ in the MS2 spectra, was confirmed by the NMR spectra, and the position was located at C-18 by comparison of the 13C-NMR shift value ( δ 70.9) with literature data, which have shown that hydroxylation at C-18 returns higher resonances ( δ 71–75) than that at C-19 ( δ 64–65) [30,31]. Moreover, hydroxylation at the equatorial substituent C-18 causes a shielding effect at C-5, as becomes clear when 2 is compared with 1 , where the hydroxylation is at C-19 (C-5: δ 43.2 in Compound 2 as compared to δ 55.9 in Compound 1 , Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The relative configuration at C-13 (i.e., assignment of a pimarane or iso-pimarane) in the case of Compound 4 could not be solved on grounds of the NOESY spectrum. However, it has been reported that pimara-8(14),15-dienes and their ent -analogues show a deshielded resonance of C-17 ( δ C about 29 ppm) in comparison with the corresponding iso-pimarane and ent -isopimarane derivatives ( δ C around 24 ppm) [31]. C-17 resonates at 29.2 ppm in Compound 4 so that it can be assigned the relative configuration of a pimarane/ ent -pimarane, i.e., the same as in Compounds 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%